Development of Interactive Learning Media Based on Augmented Reality on Swimming Material for Physical Education Learning - Saleh, Muhammad Syahrul; Saleh, Muh Sahib (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aimed to develop and evaluate an Augmented Reality (AR)-based interactive learning media to support swimming instruction in Physical Education classes at SMP Negeri 29 Makassar. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. A mixed-method approach was utilized, combining qualitative data from expert validation and user feedback with quantitative data from learning outcomes. The research subjects were 30 seventh-grade students. Validation results from media experts yielded a mean score of 92.3%, while material experts gave 90.6%, both classified as Very Valid. The practicality assessment conducted by Physical Education teachers produced a score of 88.5%, indicating that the media was Very Practical for classroom implementation. In the implementation stage, student learning outcomes significantly improved. The average pre-test score was 58.2, while the post-test score increased to 86.7, indicating a gain of 28.5 points. Statistical analysis using the paired t-test resulted in t = 11.342 with p < 0.001, confirming a significant difference. The results show that AR-based media effectively enhances students’ conceptual understanding and engagement in learning swimming skills. This media offers a promising solution for visualizing motor skills in schools lacking swimming facilities. Further research is suggested to explore its impact on other sports and education levels